The Influence Of Knowledge Of Hygiene And Sanitation On The Selection Of Student Snacks - Hidayaturrahmi, Hidayaturrahmi; Yulastri, Asmar; Fridayati, Lucy; Mustika, Sari (Universitas Negeri Padang, 2023)
The background of this research is that students in choosing snacks are more likely to choose snacks in terms of taste, appearance, shape and aroma without paying attention to hygiene and the chemicals contained in a snack. The purpose of this study was to describe the knowledge of culinary concentration students on food hygiene and sanitation, to analyze the selection of snacks for students with a culinary concentration concentration, and to analyze the influence of hygiene and sanitation knowledge on the selection of snacks for students of culinary management concentration at Padang State University. This type of research is quantitative. The sample for this research was culinary students of 2018 and 2019. The research data analysis technique was descriptive analysis, simple linear regression test, coefficient of determination test and t test. The results obtained were that students' knowledge of culinary concentration on hygiene and sanitation was in the good category as evidenced by a TCR value of 86%, Selection of student snack food patterns with a concentration of culinary arts was quite good as evidenced by a TCR value of 69%, and Knowledge of hygiene and Sanitation has a positive effect on the selection of snacks for students of culinary concentration at Padang State University as evidenced by the significance value in the simple linear regression test of 0.000 <0.05 and through the comparison of t count and t table in the t test, where the t count value is 6.126 > t table which is equal to 1.99834.